A statement on the current status and future needs of the pediatric pulmonology workforce: Pipeline Workgroup. Issue 3 (3rd November 2020) - Nelson, Benjamin A.; Boyer, Debra; Lahiri, Thomas; Oermann, Christopher M.; Rama, Jennifer A.
Abstract: There is growing concern that current trends in pediatric pulmonology will lead to a workforce shortage resulting in patients having difficulty accessing subspecialty care. As part of the Pediatric Pulmonology Division Directors Association and Pediatric Pulmonary Training Directors Association Workforce Summit, we examined factors affecting the recruitment of learners into pediatric pulmonary fellowship training (PPFT) programs. The goal of our workgroup was to describe these issues and develop a plan to increase the pipeline of learners who ultimately pursue PPFT. Specifically, we summarize factors that impact decisions to undertake PPFT, describe existing initiatives to enhance recruitment, and propose future strategies to increase early career learner interest.